2003
DOI: 10.1029/2002jc001474
|View full text |Cite
|
Sign up to set email alerts
|

Highest natural bed forms

Abstract: [1] Fluid flow interacts with sedimentary beds forming waves of different kinds, which are of considerable practical importance since they influence significantly the near-bed flow, both over and below the bed, sediment transport, and wave height attenuation. We focus here on steep bed forms capable of producing flow separation. In this case, the largescale vorticity generated in the phenomenon of separation rules the process of friction, which appears to be practically unaffected by sediment motion. Under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Sequences with larger step spacing were predominantly observed as more stable, reflecting the importance of pool development during sequence existence, which has been shown to dissipate energy through turbulence [ Gimenez‐Curto and Corniero , 2003, 2006; Wilcox et al , 2011]. By definition, the same sequence showed little changes in step spacing, so increases in either H / L or H / L / S were a result of increases in step height and scour related to pool development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences with larger step spacing were predominantly observed as more stable, reflecting the importance of pool development during sequence existence, which has been shown to dissipate energy through turbulence [ Gimenez‐Curto and Corniero , 2003, 2006; Wilcox et al , 2011]. By definition, the same sequence showed little changes in step spacing, so increases in either H / L or H / L / S were a result of increases in step height and scour related to pool development.…”
Section: Discussionmentioning
confidence: 99%
“…Step‐pool sequences best fit this relation when the distance between steps was equal to the length of the downstream pool [ Abrahams et al , 1995]. More recent data from flume experiments have shown steps form with a minimum spacing set by the exclusion zone, which is larger than the length of the associated pool [ Curran and Wilcock , 2005; Gimenez‐Curto and Corniero , 2003]. Many steps were spaced farther apart than the minimum spacing set by the exclusion zone, and thus did not fit the Abrahams relation, despite the wide parameter range possible.…”
Section: Introductionmentioning
confidence: 99%
“… Giménez‐Curto and Corniero [2006] point out that the minimum pool length, in effect the exclusion zone in the observations of Curran and Wilcock [2005], is the direct consequence of energy dissipation, or flow resistance, in very rough flows dominated by form resistance. Giménez‐Curto and Corniero [2003] show that L min (the exclusion zone) is given by in which 〈 H 〉 is the obstacle height, that is, the step height, and 〈 H 〉/ d is normalized mean drop height. Reversing the argument, when L = L min for given H (determined by available grain size), f is a maximum.…”
Section: Step Geometry Revisitedmentioning
confidence: 99%
“…Nikora (2009) extended the use of the double-averaging methodology to develop a theoretical expression that explicitly showed that the friction factor can be accounted for by six additive components, of which only three are present in two-dimensional uniform spatially-averaged flow without secondary currents: viscous stress, turbulent stress and forminduced stress. The contribution of the form-induced stress, ũw , has recently attracted substantial attention as it has been shown to play an important role in the overall streamwise momentum balance in the near-bed region (Aberle, Koll, & Dittrich, 2008;Dey & Das, 2012;Ferreira et al, 2010;GimenezCurto and Corniero, 1996;Gimenez-Curto and Corniero Lera, 2003;Manes, Pokrajac, Coceal, & McEwan, 2008;Manes, Pokrajac, & McEwan, 2007;Manes, Pokrajac, McEwan, & Nikora, 2009;Mignot, Barthelemy, & Hurther, 2009a,b;Nikora et al, 2007b;Sarkar & Dey, 2010). Indeed, Gimenez-Curto and Corniero (1996) and Gimenez-Curto and Corniero Lera (2003) suggested that at very low submergences the form-induced stress could become the dominant component in the streamwise momentum balance.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the form-induced stress, ũw , has recently attracted substantial attention as it has been shown to play an important role in the overall streamwise momentum balance in the near-bed region (Aberle, Koll, & Dittrich, 2008;Dey & Das, 2012;Ferreira et al, 2010;GimenezCurto and Corniero, 1996;Gimenez-Curto and Corniero Lera, 2003;Manes, Pokrajac, Coceal, & McEwan, 2008;Manes, Pokrajac, & McEwan, 2007;Manes, Pokrajac, McEwan, & Nikora, 2009;Mignot, Barthelemy, & Hurther, 2009a,b;Nikora et al, 2007b;Sarkar & Dey, 2010). Indeed, Gimenez-Curto and Corniero (1996) and Gimenez-Curto and Corniero Lera (2003) suggested that at very low submergences the form-induced stress could become the dominant component in the streamwise momentum balance. Interestingly Manes et al (2007) found that the relative contribution of form-induced stress increased as submergence decreased in their experiments on open channel flow over closely-packed spheres.…”
Section: Introductionmentioning
confidence: 99%